Nondestructive testing of strength of sleeve grouting material in prefabricated structure based on surface hardness method. (10th December 2020) - Gu, Sheng; Wu, Yanqi; Wang, Xidong; Li, Shengli; Ding, Chenchen; Wu, Yulong
Highlights: Correlation analysis of surface hardness and strength of grouting material. Establish the strength curve model of grouting material in PVC pipes. Laboratory and onsite experimental validation. Abstract: The strength of the sleeve grouting material plays a key role in the performance of the entire sleeve connection in prefabricated structures. Detecting this strength efficiently, reliably, and nondestructively is a difficult problem. In this research, the correlation between the surface hardness and compressive strength of a sleeve grouting material was studied first. Then, rubber stoppers with flat ends were creatively used to plug the grouting material to obtain qualified inspection surfaces, and the relationship curve between the surface hardness and compressive strength of the grouting material in PVC pipes was established. Finally, the nondestructive testing method was applied to laboratory and field testing. Results showed that the relative error between the actual values of the compressive strength obtained by the compressive tests and the conversion values of the compressive strength of the grouting material calculated from the surface hardness and strength curve was small, which satisfied the needs of practical engineering applications. The feasibility and reliability of estimating the strength of the sleeve grouting material based on the surface hardness method were further verified.